PENGARUH PEMBERIAN MADU TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM - Insani, Septa Dwi; Nasution, Naimah; Krisna, Putri (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
Maternal mortality of 10% occurs during the postpartum period and is caused by postpartum infection due to lack of wound care, 42% due to bleeding, 13% due to eclampsia and 11% postpartum complications. Perineal wounds are one of the predisposing factors for postpartum infection. Rapid healing of perineal stitches during the postpartum period is expected to prevent postpartum mothers from the dangers of infection and physiological complaints. Honey is a liquid with a distinctive sweet taste produced by honey bees that suck nectar found in flowers or in leaf axils. Honey is believed to be an alternative medicine, because it has many benefits, namely easy to digest, is a source of vitamins and minerals, especially containing vitamin C, Iron and Calcium, contains high antioxidants, essential and nonessential amino acids, and has antibiotic substances. Honey in the wound healing process is more towards anti-inflammatory, antioxidant functions, stimulates the cleaning of dead tissue. Determination of the form of honey administration for wound care must be chosen appropriately so that the potential of honey can be utilized optimally. The purpose of this study was to determine the effectiveness of honey to accelerate the healing of perineal wounds in postpartum mothers. This study was conducted using a descriptive analytical method with a quasi-experiment. Respondents consisted of 20 physiological postpartum mothers. Data were obtained through interviews and observations. The results showed that perineal wound care using honey resulted in 12 respondents (60%) experiencing slow wound healing and 8 respondents (40%) experiencing fast wound healing. Honey can be recommended for healing perineal wounds in postpartum mothers because it has been proven effective in accelerating wound healing.